Optimizing the production and efficacy of antimicrobial bioactive compounds from Streptomyces kanamyceticus in combating multi-drug-resistant pathogens - Shang, Zifang; Sharma, Vipasha; Pai, Liu; Kumar, Tarun; Patil, Sandip (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThe rise of antibiotic-resistant pathogens has intensified the search for novel antimicrobial agents. This study aimed to isolate Streptomyces kanamyceticus from local soil samples and evaluate its antimicrobial properties, along with optimizing the production of bioactive compounds.MethodsSoil samples were collected from local regions, processed, and analysed for Streptomyces strains isolation using morphological characteristics and molecular identification through 16S rRNA gene PCR assay. Antimicrobial activity was assessed against Escherichia coli, Staphylococcus aureus, Bacillus subtilis, and Candida albicans using the double-layer method, while Minimum Inhibitory Concentration (MIC) values were determined. The extracted compounds underwent Fourier Transform Infrared Spectroscopy (FTIR) analysis for functional group identification. Optimization of bioactive compound production was performed using a Central Composite Design (CCD) coupled with Partial Least Squares Regression (PLSR).ResultsA total of 25 distinct Streptomyces strains were isolated, with seven confirmed as S. kanamyceticus. These strains exhibited antimicrobial activity, with inhibition zones reaching 30 mm and MIC values between 20 and 70 µg/mL. The extraction yielded 150-200 mL of bioactive compounds. Optimization studies revealed that a medium containing 10 g/L glucose and 10 g/L glycine max meal maximized antibiotic production.ConclusionThis study confirmed that S. kanamyceticus is a promising source of novel antibiotics. The combination of microbial isolation, antimicrobial testing, and statistical optimization successfully enhanced the production of bioactive compounds, contributing to the search for effective antimicrobial agents against resistant pathogens.